The Role of Pretrial Procedures in Protecting Human Rights in Indonesia - Limbong, Andrew Afrizal; Debora (Universitas Darussalam Gontor, 2024)
**English**Law enforcement and its execution in Indonesia remain far from ideal. The primary weakness lies not in the legal system or its instruments but in the enforcement itself. Coercive tactics often employed by law enforcement officers during investigations are among the key issues. Pretrial proceedings were established to protect the human rights of suspects during the investigation process. This study aims to examine the role of pretrial proceedings in safeguarding human rights and the extent to which they can reduce abuses of power by law enforcement authorities. The research outlines two main problems: (1) How do pretrial proceedings protect the human rights of suspects? (2) To what extent can pretrial proceedings minimize the misuse of power by law enforcement officers? The research adopts a normative legal method, also known as library research, focusing on the study of legal norms and principles. The findings reveal that pretrial proceedings are a significant legal instrument for protecting human rights in Indonesia. Despite challenges in implementation, optimizing pretrial proceedings through improved judicial capacity, public awareness, and regulatory reforms can strengthen their role as a human rights safeguard. Thus, pretrial proceedings can serve as an effective shield for upholding justice and protecting individuals' rights from unlawful actions. **Indonesia**Penegakan beserta eksekusi hukum di Indonesia masih jauh dari kata ideal. Penegakan hukum di negara ini, bukan sistem hukum ataupun perangkat hukumnya, ialah kelemahan utamanya. Taktik pemaksaan yang diterapkan penegak hukum selama penyelidikan ialah salah satunya. Lembaga Praperadilan didirikan guna melindungi hak asasi tersangka selama proses penyidikan. Penelitian ini tujuannya guna mengetahui peran praperadilan dalam perlindungan hak asasi manusia dan sejauh mana praperadilan dapat mengurangi penyalah gunaan kekuasaan oleh aparat penegak hukum. Berdasarkan penelitian tersebut, penulis mengajukan rumusan masalah: 1. Bagaimana peran praperadilan dalam melindungi hak asasi tersangka, 2. Sejauh mana praperadilan dapat mengurangi penyalahgunaan kekuasaan yang dilakukan aparat penegak hukum. Jenis metode penelitian ini adalah penelitian normatif atau yang di sebut juga dengan penelitian penelitian hukum perpustakaan atau library research. Hasil penelitian ini bahwa Praperadilan merupakan instrumen hukum yang signifikan dalam melindungi hak asasi manusia di Indonesia. Meskipun terdapat kendala dalam implementasinya, optimalisasi praperadilan melalui peningkatan kapasitas hakim, sosialisasi, dan perbaikan regulasi dapat memperkuat peran lembaga ini sebagai penjaga HAM. Dengan begitu, praperadilan dapat menjadi benteng yang efektif dalam menjaga keadilan dan melindungi hak-hak individu dari tindakan yang melanggar hukum.